Increased Plasma Caspase-3 in Children with Down Syndrome is Associated with an Increasing Risk of Pulmonary Hypertension - Prasanti, Damayanti Ika; Widjaja, Sri Lilijanti; Rokhayati, Evi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Pulmonary hypertension (PH) is the one of the comorbidities in children with Down syndrome. The pathogenesis of this pulmonary hypertension remains to be investigated, although endothelial dysfunction and apoptotic activity are among the proposed mechanisms. Caspase-3 is a key regulator of apoptosis and appears to be an attractive predictor of pulmonary hypertension in children with Down syndrome. Subjects and Method: A cross-sectional observational clinical study was performed in Dr. Moewardi General Hospital in Surakarta-Indonesia between January and March 2021 involving clinically diagnosed children with Down syndrome. Sampling method was using a consecutive sampling. The independent variable was plasma caspase-3 level and the dependent variable were the presence of pulmonary hypertension and congenital heart defects (CHD). Clinical data documentation, blood collection and echocardiography were performed on enrollment day. We first determined the plasma level of caspase-3 in 36 children with Down syndrome and CHD (n=18) or without CHD (n=18) and further determined the risk of having pulmonary hypertension using the plasma caspase-3 level. We also determined the biomarker performance of caspase-3 using a receiver-operating characteristic (ROC) analysis Results: Children with Down syndrome with PH had a higher plasma caspase-3 compared to those without PH (p<0.001). In those with both CHD and PH, the plasma caspase-3 level was also high although not statistically significant (p=0.145). The highest plasma caspase-3 level was observed in subjects with PH without CHD (p<0.01). Relative risk and ROC analysis demonstrated that increased plasma caspase-3 level increased the risk to have PH 5 times (RR=5.00, 95% CI 1.74 to 14.34; p<0.001) and predicted the incidence of PH in children with Down syndrome (AUC 0.88, CI 0.76 to 0.99). Conclusion: An elevation in plasma caspase-3 level of Down syndrome children is associated with the increasing risk of having PH regardless the presence of CHD. Keywords: pulmonary hypertension; down syndrome; caspase-3; pathogenesis; apoptosis. Correspondence: Damayanti Ika Prasanti. Department of Pediatrics, Faculty of Medicine, Universitas Sebelas Maret / Dr. Moewardi General Hospital. Jl. Kolonel Sutarto 132, Surakarta 57126, Indonesia. Email: damayanti_ip@yahoo.com. Mobile: 081215683462.